Implementation of Seismic Ground Response Analysis in Estimating Liquefaction Potential in Northern Thailand - Mase, Lindung Zalbuin; Likitlersuang, Suched (Indonesian Journal on Geoscience, 2021)
It has been known that northern Thailand is an active tectonic region in Southeast Asia. Some earthquakes with low to medium magnitudes had occurred in northern Thailand. The Mw6.1 Mae Lao Earthquake occurred on May 5th, 2014 in Chiang Rai Province. The earthquake also resulted in the unique phenomenon of ground failure, which was known as liquefaction. Learning from the event, the liquefaction potential based on seismic ground response analysis was performed. Several site investigations including standard penetration test and seismic down-hole test in Chiang Rai Province were carried out. The next generation attenuation model was conducted to generate the ground motion for nonlinear seismic response analysis. The peak ground acceleration at the ground surface from seismic ground response analysis was used to analyze the empirical analysis of liquefaction potential. The results show that liquefaction could occur at the investigated locations during the earthquake. The results also confirm the liquefaction evidence found in Chiang Rai Province during the Mw 6.1 Mae Lao Earthquake. This research can help the people to consider the earthquake impacts to northern Thailand.